2020
DOI: 10.1002/aenm.202002124
|View full text |Cite
|
Sign up to set email alerts
|

Field Effect versus Driving Force: Charge Generation in Small‐Molecule Organic Solar Cells

Abstract: Efficient charge generation in organic semiconductors usually requires an interface with an energetic gradient between an electron donor and an electron acceptor in order to dissociate the photogenerated excitons. However, single‐component organic solar cells based on chloroboron subnaphthalocyanine (SubNc) have been reported to provide considerable photocurrents despite the absence of an energy gradient at the interface with an acceptor. In this work, it is shown that this is not due to direct free carrier ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 47 publications
(55 reference statements)
2
26
0
Order By: Relevance
“…[46] However, this hypothesis has been questioned in a more recent work. [74] On the basis of the absence of charge photogeneration observed on pristine SubNc films, it was concluded that the process of charge generation is a field-assisted exciton dissociation specific of the device configuration and not an intrinsic property of the material. [74] However, based on the observed large magnitude of this field-effect, it was proposed that in certain neat organic semiconductors, this effect can lead to efficient photocurrent generation even though the driving force is minimized and the open-circuit voltage is maximized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] However, this hypothesis has been questioned in a more recent work. [74] On the basis of the absence of charge photogeneration observed on pristine SubNc films, it was concluded that the process of charge generation is a field-assisted exciton dissociation specific of the device configuration and not an intrinsic property of the material. [74] However, based on the observed large magnitude of this field-effect, it was proposed that in certain neat organic semiconductors, this effect can lead to efficient photocurrent generation even though the driving force is minimized and the open-circuit voltage is maximized.…”
Section: Discussionmentioning
confidence: 99%
“…[74] On the basis of the absence of charge photogeneration observed on pristine SubNc films, it was concluded that the process of charge generation is a field-assisted exciton dissociation specific of the device configuration and not an intrinsic property of the material. [74] However, based on the observed large magnitude of this field-effect, it was proposed that in certain neat organic semiconductors, this effect can lead to efficient photocurrent generation even though the driving force is minimized and the open-circuit voltage is maximized. [74] In fact, the built-in electric field provided by the interlayers/contacts has been reported to contribute to exciton dissociation in BHJ cells based on a low bandgap polymer and PC 71 BM with low driving energy or in high efficiency BHJs based on NFA.…”
Section: Discussionmentioning
confidence: 99%
“…As another probe of free charge generation in Y6, we perform optical-pump-terahertz probe (OPTP) spectroscopy. 40,41 Figure 2e shows the conductivity spectrum at 3 ps probe delay of a neat film of Y6, excited with an 800 nm pump beam, at an excitation density of ~5×10 15 excitations/cm 3 . The non-zero real part of the terahertz (THz) spectrum (light blue line) is indicative of a fraction of free polarons, rather purely bound excitons.…”
Section: Exciton -Charge Dynamics and Equilibriummentioning
confidence: 99%
“…For the last thirty years, 4,12 this constraint has guided the development of organic photovoltaics (OPVs)which promise a step-change in flexible, lightweight, non-toxic solution-processed solar energy production, but are yet to be widely commercialised. Splitting bound excitons into free charges has required sharp molecular heterojunctions between donor and acceptor materials (though some have recently shown field-assisted exciton dissociation, or CT-state/polaron-pair formation [13][14][15][16] ). Rather than purely optimising charge harvesting, OPV devices have been optimised for exciton splitting at interfaces, and demand complex interpenetrating networks of donor and acceptor materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation